Resilience in the Classroom: A Qualitative Inquiry on How Parental Separation Affects College Students' Learning and Their Coping Abilities - Redulfin, Genevieve; Tenebroso, Desiree C.; Tagare Jr., Ruben L.; Siocon, Ana Trisha F.; Gaspar, Rishel Lyn P.; Adlaon, Gauvin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to examine the impact of parental separation on the academic experiences of Bachelor of Physical Education students, focusing on how it influences their learning, engagement, and overall academic performance. By exploring both the challenges they face and the coping strategies they employ, the study seeks to provide a deeper understanding of the educational implications of parental separation and contribute to the development of targeted support systems for affected students. Methodology: A qualitative approach was used to gain an in-depth understanding of the participants' experiences. Interviews were conducted among 25 Bachelor of Physical Education students using a validated set of open-ended guide questions. The interviews were recorded, transcribed, and translated to ensure accuracy and consistency in data interpretation. For data analysis, thematic analysis was employed, allowing the researchers to identify recurring patterns, themes, and significant insights related to the effects of parental separation on students' learning and coping mechanisms. This systematic approach ensured that the findings were grounded in the participants' lived experiences, providing a comprehensive understanding of the phenomenon. Main Findings: The study identified five significant effects of parental separation on students: loss of focus, feeling depressed, missing classes, studying hard to reach goals, taking the situation positively, lack of financial support, delays in submitting schoolwork, reduced moral support from parents, and even dropping out of school. In terms of coping mechanisms, the participants identified five main strategies: engaging in physical activities, strengthening their faith in God, using the situation as motivation, surrounding themselves with supportive people, staying brave and keeping away from negativity, and remaining positive by going with the flow and being grateful. Novelty/Originality of this study: The study highlights the significant impact of parental separation on students’ academic performance and identifies physical activity as an effective coping mechanism. It provides valuable insights into the experiences and resilience strategies of Bachelor of Physical Education students, offering a culturally relevant perspective in the context of the Philippines.